10+(-3.5)x2+(-9)/(-3)

Answers

Answer 1
Answer: I simplified and I got -3.5x^2+13

Related Questions

HELP PLEASE!! What are the domain and range of each relation? Drag the answer into the box to match each relation
What is the least common denominator of 1/3 and 5/11? 25 points
A fish tank contains 18 goldfish and 22 guppies. If you randomly select 2 fish, what is the probability that they are both goldfish?
Mrs.Prescott has 12 oranges. She puts 2 oranges in each bag. How many bags does she have?
Two landscapers must mow a rectangular lawn that measures 100 feet by 200 feet. Each wants to mow no more than half of the lawn. The first starts by mowing around the outside of the lawn. How wide a strip must the first landscaper mow on each of the four sides in order to mow no more than half of the lawn? The mower has a 24-inch cut. Approximate the required number of trips around the lawn.

What is the perimeter of a rhombus-shaped street sign with 35-cm side?

Answers

rhombus has 4 sides htat are equal legnth
if 1 side is 35
all 4 sides are 35
perimiter=legnth around=4 times 35=140
answer is 140cm

The equation x2 + y2 − 2x + 2y − 1 = 0 is the general form of the equation of a circle. What is the standard form of the equation?

Answers

Answer:

(x-1)^2+ (y+1)^2=3

Step-by-step explanation:

x^2 + y^2 - 2x + 2y - 1 = 0

Standard form of the equation is (x-h)^2 + (y-k)^2= r^2

To get standard form we apply completing the square method

x^2-2x+ y^2+ 2y - 1 = 0

Take coefficient of x  and y . Divide it by 2 and then square it

(2)/(2) =1 and 1^2=1

Add and subtract 1

(x^2-2x)+(y^2+ 2y) - 1 = 0

(x^2-2x+1-1)+(y^2+ 2y+1-1) - 1 = 0

(x^2-2x+1)+(y^2+ 2y+1)-1-1- 1 = 0

(x^2-2x+1)+(y^2+ 2y+1)-3= 0

Now write the parenthesis in square form

(x-1)(x-1)+ (y+1)(y+1)-3= 0

(x-1)^2+ (y+1)^2-3= 0 , add 3 on both sides

(x-1)^2+ (y+1)^2=3 is the standard form

x^2 + y^2 - 2x + 2y - 1 = 0

(x^2 - 2x) + (y^2 + 2y) - 1 = 0

(x^2 - 2x + 1) + (y^2 + 2y + 1) - 1 - 1 - 1 = 0

(x - 1)^2 + (y + 1)^2 - 3 = 0

(x - 1)^2 + (y + 1)^2 = 3


What is the simplified form of the quantity 4 z squared minus 4z minus 15 over the quantity 2 z squared plus z minus 15? (6 points)

Answers

Answer: The simplified form of the given equation is (2z+3)/(z+3)

Step-by-step explanation:

From the given information, the numerator of the given fraction is: 4z^2-4z-15

and denominator of the given fraction is 2z^2+z-15

The fraction becomes:

(4z^2-4z-15)/(2z^2+z-15)

Applying middle term factorization in the numerator and denominator term, we get:

= (4z^2-10z+6z-15)/(2z^2+6z-5z-15)

= (2z(2z-5)+3(2z-5))/(2z(z+3)-5(z+3))

= ((2z+3)(2z-5))/((2z-5)(z+3))

Cancelling (2z-5) factor from numerator an denominator, we get:

= (2z+3)/(z+3)

The above fraction is the simplified form of the equation formed in the question.

First you simplify it down to (2z+3)(2z-5)/(2z-5)(z+3)
Both of the brackets containing (2z-5) can now be cancelled out leaving you with a final answer of (2z+3)/(z+3)

What is the sum of the given polynomials in standard form?
(x2 – 3x) + (–2x2 + 5x – 3)

Answers

Answer:

-x^2+2x-3

Step-by-step explanation:

We have (x^2- 3x) + (-2x^2 + 5x -3) which is the same as:

x^2-3x-2x^2+5x-3

The polynomial has 5 terms that we are going to analyse:

1st. term: x^2       Degree: 2   Coefficient: 1

Observation: Coefficient is the number in front of a variable. In this case the variable is x. Then the first term has coefficient 1 because (1).x^2=x^2.

2nd. term: -3x     Degree:1     Coefficient: (-3)

3rd. term: -2x^2  Degree:2    Coefficient: (-2)

4th. term: 5x      Degree:1     Coefficient: 5

5th. term: -3        Degree:0    Coefficient: (-3)

We have to reorder the polynomial writing each term in order of degree from highest to lowest (left to right).

The terms with highest degree are the first and third. Then the second and fourth term. And the lowest degree  corresponds to the fifth term.

The polynomial now is:

x^2-2x^2-3x+5x-3

Now we have to sum the terms that have the same degree:

x^2-2x^2=(1-2)x^2=(-1)x^2=-x^2

-3x+5x=(-3+5)x=2x

Then the result is:

-x^2+2x-3

-x2 + 2x - 3 is the final answer to that

Help me again please.

Answers

Answer:

m=(8)/(5)

Step-by-step explanation:

What is a simple formula to solve a math sequence? Or a couple formulas if possible? Thanks!

Answers

2 normal types of sequences:

1. arythmetic sequences: each term is the same distance to the next term, example, 2,4,6,8, distance is 2

2. geometric sequences: the ratio of consecutive terms is the same, example: 2,4,8,16, ratio is 4:2=2:1, 2/1=2


the nth term is denoted by a_(n)
the first term is represented by a_(1)

for arythmetic sequences, the nth tem is
a_(n)=a_(1)(n-1)d where d=distance between each term

for geometric sequences the nth term is
[tex] a_{n}=a_{1}r^{n-1} where r=ratio betwen consecutive terms